2002
DOI: 10.1136/gut.51.6.864
|View full text |Cite
|
Sign up to set email alerts
|

Retreatment with interferon plus ribavirin of chronic hepatitis C non-responders to interferon monotherapy: a meta-analysis of individual patient data

Abstract: Background and aims: Retreatment with a combination of α interferon (IFN) plus ribavirin of patients with chronic hepatitis C who did not respond to IFN monotherapy has not been assessed in large controlled studies. Methods: To assess the effectiveness and tolerability of IFN/ribavirin retreatment of non-responders to IFN and to identify predictors of complete (biochemical and virological) sustained response, we performed a meta-analysis of individual data on 581 patients from 10 centres. Retreatment with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
(27 reference statements)
0
16
1
Order By: Relevance
“…In previous studies, the mean patient age was 41-45 years, 7,8,[10][11][12][13][14]23 lower than that in our study. Although subpopulations according to patient age are not known for previous studies, our results indicated that the subpopulation of older patients was greater in our study than in these earlier reports.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In previous studies, the mean patient age was 41-45 years, 7,8,[10][11][12][13][14]23 lower than that in our study. Although subpopulations according to patient age are not known for previous studies, our results indicated that the subpopulation of older patients was greater in our study than in these earlier reports.…”
Section: Discussioncontrasting
confidence: 81%
“…7,8,14,23 The proportion of patients requiring ribavirin dose reduction was reported to be 6% to 20%. [7][8][9][10]23 In our study, the mean maximal decrease was 4.0 g/dl (range, 0.2-7.6 g/dl), which was greater than those reported previously. This result suggests that patients with lower baseline Hb levels will decrease to levels of less than 10 g/dl more easily compared with those with higher baseline Hb levels, and therefore will more frequently require ribavirin dose reduction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A meta-analysis that evaluated the efficacy of conventional IFN and ribavirin combination therapy in previous nonresponders reported only 13% SVR, thus indicating the need for better therapeutic options [8].…”
mentioning
confidence: 99%
“…8 Re-treatment with similar regimen after the initial failure is not an optimal choice as the outcome is relatively poor. 9,10 Furthermore, the IFN-α based treatment is not without side effects. Patients often have to discontinue treatment due to intolerable side effects or reduce the treatment dosages to minimize such effects.…”
Section: Introductionmentioning
confidence: 99%